Path analysis Faktor Budaya dengan Stunting melalui Pola Asuh pada Balita di Muna Barat, Sulawesi Tenggara: Stunting - Wahidah Rohmawati; Dian Rosmala Lestari (Journal of sciences and health, 2021)
Background: Stunting is a hidden problem caused by chronic nutritional deficiencies during the first 1,000 days of child's life. Stunting resulted in irreversible growth and development, i.e., the child cannot develop the potential and capability in themselves optimally. The evidence shows that stunting has short-term and long-term impacts such as health disorders, low learning achievement in schools, low-quality human resources and low household income as well as increased risk cardiovascular disease in adulthood. The purpose of this research is to analyze the direct and indirect influence of knowledge, occupation, culture of stunting through the parenting pattern in toddlers. Method: The types of this study are quantitative research design with case control study approach and using path analysis. The population in this study is all toddlers in Muna Barat while the number of samples is as much as 100 toddlers aged 6-59 months in the Puskesmas area Marobea, Sidamangura and Tiworo Tengah. Sampling techniques with fixed disease sampling. Results: The influential culture typically indirectly to stunting through parenting pattern with value (b=2.24; CI 95%=1.68 to 3.69; p=0.000). Conclusions: Culture is the most influential factor in stunting with the mediated parenting pattern, the total value of the effect of indirect influence is (3.20). Keywords: Culture, Parenting, Stunting